Predictive factors of subject well-being in older people - Torres Palma, William Ignacio (2018)
This study assessed the effect of variables such as life satisfaction, self-rated health, social support and coping styles on subjective well-being. The level of subjective well-being was studied in a sample of Mexican elderly persons from the state of Yucatan in Merida (n = 122) with an age range of 60-93 years. The results in women show that coping styles predicts subjective well-being in negative affects. Moreover, self-perception of health, coping styles, and satisfaction with life are adequate predictors of the cognitive dimension of subjective well-being. Results in men show that satisfaction with life and coping styles predict the cognitive dimension of subjective well-being. Findings point to the importance of exploring psychosocial variables in older adults.